Neigungen zu psychischen Erkrankungen?: Jüdische Patientinnen und Patienten in psychiatrischen Heilanstalten vor dem Ersten Weltkrieg - Vanja, Christina (Aschkenas, 2019)
The years around 1900 were marked by discussions on whether Jews were particularly susceptible to mental suffering. Not only was the topic presented by racial hygienists with anti-Semitic hrust, it also played a prominent role for Jewish physicians. The causes of »Jewish nervousness« were discussed controversially, either as a hereditary biological system of the Jewish »race« or as caused by the specific history of Jews in exile, where they lived in an anti-Semitic environment, or their particular urban lifestyle that was alienated from nature, or a tendency to mental illness. The »Israelite Health and Nursing Establishment« in Bendorf-Sayn understood itself as an institution that specialized in the needs of Jewish patients and kept them safe from anti-Semitic attacks. However, it was only intended for a solvent clientele. In public welfare institutions patients of Jewish faith generally could not expect any concessions and were discriminated against, in particular by psychiatrists oriented towards racial hygiene.